(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO (B: (3abO GdJeS efi HYV NdU ENhGfi hef jdRefi ESYGag , HeG jSeM Hg s
(3BNQgG (B:s
(3ceGd GdEYJOGd GdEfSGfi ai ehGLgI hHGdbjGS ai HOf GdChRGg hcPdc s
(3bWYI CNQi JHJOF HChd GdcJGH hJfJgi CKfGA GdaUd GdKdGKjf hHYV UaMGJgG MGFdI Gddhf ef CKQ GdQWhHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B812 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B144 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1311s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs